Heuristics for the Solution of a Very Large Street Routing Problem with Mixed Transportation Mode - Matis, Peter (Communications - Scientific letters of the University of Zilina, 2009)
Servicing a large number of customers in a city zone is often a considerable part of many logistics chains. This problem is called a Street Routing Problem (SRP). As presented, only using systems such as Geographical Information Systems (GIS) it is possible to effectively manage SRP. New heuristic for solving a very large SRP is evaluated on the real data. One of the key properties of GIS for use with the routing software is its flexible interactive and user-friendly environment. The paper presents several approximations of length for SRP with mixed transportation mode.